GENEROS DE BRACONIDAE (INSECTA: HYMENOPTERA) DEPOSITADOS EN LA COLECCION ENTOMOLOGICA DEL INSTITUTO DE FITOSANIDAD DEL COLEGIO DE POSTGRADUADOS - Sánchez García, José Antonio; López Martínez, Víctor (Instituto de Ecología, A.C., 2000)
We made a checkiist of braconids of the Colección Entomológica del Instituto de Fitosanidad del Colegio de Postgraduados (CEIFIT). A list of 92 genera in 40 tribes and 20 subfamilias of braconids was obtained. From these genera, Schoenlandella is a new report from México. The most abundant genera were Aphidius, Opius, Apanteles, Diaeretiella and Aleiodes. The most representativo (because its high number of species) genera were Opius, Bracon and Apanteles. The most representativo subfamilias were Alysiinae and Doryctinae in the colección del CEIFIT. Species from the genera Aphidius, Diaeretiella, Lysiphiebus, Praon, Trioxys, Habrobracon, Chelonus, Cotesia and Diachasmimorpha, were found to be parasitic on different pest species of economic importance.